Comparing urine samples and cervical swabs for Chlamydia testing in a female population by means of Strand Displacement Assay (SDA) - Wentzel-Larsen Tore; Fosse Beata; Thune Turid; Haugland Siren; Hjelmevoll Stig; Myrmel Helge (BMC, 2010)
Abstract Background There has been an increasing number of diagnosed cases of Chlamydia trachomatis in many countries, in particular among young people. The present study was based on a growing request to examine urine as a supplementary or primary specimen in screening for Chlamydia trachomatis in women, with the Becton Dickinson ProbeTec (BDPT) Strand Displacement Assay (SDA). Urine samples may be particularly important in screening young people who are asymptomatic. Methods A total of 603 women aged 15 and older were enrolled from the Sexually Transmitted Infection (STI) clinic at Haukeland University Hospital, Norway, in 2007. Only 31 women were older than 35 years. Cervical swabs and urine samples were tested with BDPT for all participants. In cases of discrepant test results from a given patient, both samples were retested by Cobas TaqManCT and a Polymerase Chain Reaction (PCR)-method (in-house). Prevalence of C. trachomatis, sensitivity, and specificity were estimated by latent class analysis using all test results available. Bootstrap BC confidence intervals (10 000 computations) were estimated for sensitivity and specificity, and their differences in cervix vs. urine tests. Results A total of 1809 specimens were collected from 603 patients. 80 women (13.4%) were positive for C. trachomatis. Among these, BDPT identified 72 and 73 as positive in cervix and urine samples, respectively. Of the 523 C. trachomatis negative women, BDPT identified 519 as negative based on cervical swabs, and 514 based on urine samples. Sensitivity for cervical swabs and urine samples with the BDPT were 89.0% (95% CI 78.8, 98.6) and 90.2% (95% CI 78.1, 95.5), respectively. The corresponding values for specificity were 99.2% (95% CI 98.3, 100) and 98.3% (95% CI 96.4, 100). Conclusions This study indicates that urine specimens are adequate for screening high-risk groups for C. trachomatis by the SDA method (BDPT). Such an approach may facilitate early detection and treatment of the target groups for screening, and be cost-effective for patients and the health services.